2016
DOI: 10.1007/s00424-016-1856-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic exposure to high palmitic acid concentrations on the aerobic metabolism of human endothelial EA.hy926 cells

Abstract: A chronic elevation of circulating free fatty acids (FFAs) is associated with diseases like obesity or diabetes and can lead to lipotoxicity. The goals of this study were to assess the influence of chronic exposure to high palmitic acid (PAL) levels on mitochondrial respiratory functions in endothelial cells and isolated mitochondria. Human umbilical vein endothelial cells (EA.hy926 line) were grown for 6 days in a medium containing either 100 or 150 μM PAL. Growth at high PAL concentrations induced a consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…In addition, the elevated expression levels of mitochondrial superoxide dismutase (SOD2) and uncoupling protein 2 (UCP2), the antioxidative system proteins, probably help to maintain the unchanged levels of mitochondria-produced ROS, although ATOR-induced changes in the respiratory chain are conducive to increased mROS production. We have previously shown that one physiological role of UCP2 in endothelial cells could be the attenuation of mROS production under conditions of excessive oxidative stress, such as exposure to high glucose or palmitic acid concentrations [29,30]. The results of this study indicate that one physiological role of UCP2 in endothelial mitochondria could be the attenuation of mROS production, in addition to maintaining an unchanged level of ROS production by mitochondria.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In addition, the elevated expression levels of mitochondrial superoxide dismutase (SOD2) and uncoupling protein 2 (UCP2), the antioxidative system proteins, probably help to maintain the unchanged levels of mitochondria-produced ROS, although ATOR-induced changes in the respiratory chain are conducive to increased mROS production. We have previously shown that one physiological role of UCP2 in endothelial cells could be the attenuation of mROS production under conditions of excessive oxidative stress, such as exposure to high glucose or palmitic acid concentrations [29,30]. The results of this study indicate that one physiological role of UCP2 in endothelial mitochondria could be the attenuation of mROS production, in addition to maintaining an unchanged level of ROS production by mitochondria.…”
Section: Discussionmentioning
confidence: 50%
“…The mitochondrial function of detached EA.hy926 cells was determined polarographically, as previously described [29,40]. The following respiratory substrates were used: 5.5 mM glucose, 5 mM pyruvate, 3 mM glutamine, a mixture of 5 mM pyruvate and 3 mM glutamine, or 0.3 mM palmitate.…”
Section: Measurements Of Cell Respirationmentioning
confidence: 99%
“…In this study, we chose PA as stimulus because PA is the dominant saturated fatty acids and highly links to AS. Meanwhile, literates have shown PA could induce mitochondrial fission in endothelial cells, leading to endothelial dysfunction (Broniarek et al, ). However, the effect of ox‐LDL on mitochondrial fission still needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FAs are recognized as primary stimulators of ROS production that is caused by disturbances in the synthesis of cardiolipin, mitochondrial uncoupling, and diacylglycerol-dependent protein kinase C and NADPH oxidase activation, which negatively affect both vascular tone and cell growth [88,93,95]. Endothelial dysfunction was observed in obese ZDF rats and palmitate-exposed human umbilical vein endothelial cells and the EA.hy926 cell line and associated with FA-induced NADPH oxidase subunit overexpression and ROS production [96,97]. The treatment of EA.hy926 cells with high levels of palmitic acid resulted in excessive oxidative stress and Ca 2+ -dependent autophagy and necrotic cell death [97,98].…”
Section: Fatty Acid Metabolites and Endothelial Exhaustionmentioning
confidence: 99%
“…Endothelial dysfunction was observed in obese ZDF rats and palmitate-exposed human umbilical vein endothelial cells and the EA.hy926 cell line and associated with FA-induced NADPH oxidase subunit overexpression and ROS production [96,97]. The treatment of EA.hy926 cells with high levels of palmitic acid resulted in excessive oxidative stress and Ca 2+ -dependent autophagy and necrotic cell death [97,98].…”
Section: Fatty Acid Metabolites and Endothelial Exhaustionmentioning
confidence: 99%